Enhancing speaking skills amidst and beyond the Covid-19 pandemic: Innovative strategies from teachers’ perspectives for high school EFL learners - Suryanto, Suryanto; Purwanti, Eko; Dewanti , Felansonia Azhima (English Language Teaching Educational Journal, 2023)
The success of English language learners is determined by their capacity for effective English communication. The purposes of this study are firstly to examine what activities university teachers employ to enhance students’ speaking skills during and post-COVID-19 pandemic and secondly investigate the differences in teaching speaking skills during and post-COVID pandemic. The researchers select seven English instructors as participants using a qualitative descriptive research design. All participants were English lecturers at a Yogyakarta private university. Participants include three female and four male teachers taken using purposive sampling method. Using an interview guide, the researchers conducted interviews with the participants to collect data. The findings show ten activities lecturers utilize to instruct speaking skills during and post-pandemic. The activities include giving speaking practices, making group work activities, retelling stories, or experiences, assigning role play and presentations, asking students to record activities, providing communicating exposures, practicing interviews, and producing a vlog. During and post the pandemic, the second set of findings highlights the differences in teaching speaking during and post pandemics, covering the nature of the activities in terms of flexibility, degree of control, and engagement.